Investigation of the processes of dust processing gas cleaning of steelmaking industries - S. L. Rimoshevsky; D. A. Prokopchuk; D. M. Golub (Литьë и металлургия, 2021)
The article deals with the issues of processing of dust from electric steelmaking production by the method of thermodynamic extraction of iron, zinc and lead in order to reduce the environmental impact and increase the resource base of the industry. The paper presents various methods of zinc extraction from dust and gas purification, thermodynamic calculation of the decomposition and reclaiming of zinc ferrite.